ErKon3D - quantifying deformation in Aegean sealing practices [dataset] - Mara, Hubert (Universität, 2023)
In Bronze Aegean society, seals played an important role by authenticating, securing and marking. The study of the seals and their engraved motifs provides valuable insight into the social and political organization and administration of Aegean societies. A key research question is the determination of authorship and origin. Given several sets of similar impressions with a wide geographical distribution on Crete, and even beyond the island, the question arises as to whether all of them originated from the same seal and thus the same seal user. Current archaeological practice focuses on manually and qualitatively distinguishing visual features. In this work, we quantitatively evaluate and highlight visual differences between sets of seal impressions, enabling archaeological research to focus on measurable differences. Our data are plasticine and latex casts of original seal impressions acquired with a structured-light 3D scanner. Surface curvature of 3D meshes is computed with Multi-Scale Integral Invariants (MSII) and rendered into 2D images. Then, visual feature descriptors are extracted and used in a two-stage registration process. A rough rigid fit is followed by non-rigid fine-tuning on basis of thin-plate splines (TPS). We compute and visualize all pairwise differences in a set of seal impressions, making outliers easily visible showing significantly different impressions. To validate our approach, we construct a-priori synthetic deformations between impressions that our method reverses. Our method and its parameters is evaluated on the resulting difference. For testing real-world applicability, we manufactured two sets of physical seal impressions, with a-priori known manufactured differences, against which our method is tested. (2020-02-20)